Bone Marrow Aspirate Concentrate-Enhanced Marrow Stimulation of Chondral Defects - Henning Madry; Liang Gao; Hermann Eichler; Patrick Orth; Magali Cucchiarini (Stem Cells International)
Mesenchymal stem cells (MSCs) from bone marrow play a critical role in osteochondral repair. A bone marrow clot forms within the cartilage defect either as a result of marrow stimulation or during the course of the spontaneous repair of osteochondral defects. Mobilized pluripotent MSCs from the subchondral bone migrate into the defect filled with the clot, differentiate into chondrocytes and osteoblasts, and form a repair tissue over time. The additional application of a bone marrow aspirate (BMA) to the procedure of marrow stimulation is thought to enhance cartilage repair as it may provide both an additional cell population capable of chondrogenesis and a source of growth factors stimulating cartilage repair. Moreover, the BMA clot provides a three-dimensional environment, possibly further supporting chondrogenesis and protecting the subchondral bone from structural alterations. The purpose of this review is to bridge the gap in our understanding between the basic science knowledge on MSCs and BMA and the clinical and technical aspects of marrow stimulation-based cartilage repair by examining available data on the role and mechanisms of MSCs and BMA in osteochondral repair. Implications of findings from both translational and clinical studies using BMA concentrate-enhanced marrow stimulation are discussed.